Lexikos and AFRILEX — A Perfect Lexicographic Liaison - Alberts, Mariëtta (Lexikos, 2022)
After in-depth discussions with interested parties in 1991 the Bureau of the Woordeboek van die Afrikaanse Taal (WAT) realized that the future of Afrikaans is inextricably connected with that of the other existing and utilized languages in South Africa. One of the results of the discussions was the establishment in 1991 of an academic journal Lexikos in the AFRILEX Series. An external feasibility study was also conducted on behalf of the Board of Control of the Bureau of the WAT to determine the possibility for the establishment of an Institute for Southern African Lexicography. The results of the feasibility study indicated that respondents did not want another bureaucratic institution. A major result of the feasibility study, however, was the establishment in 1995 of a professional association, the African Association for Lexicography, that concentrates exclusively on lexicographical issues. The Bureau of the WAT gave permission to the new association to use the acronym "AFRILEX". The Pan-South African Language Board (PanSALB), also established in 1995, was a direct consequence of the country's new multilingual dispensation. The legislation governing PanSALB was amended to allow for equal justice to all dictionary projects for the official South African languages. This led to the establishment of national lexicography units for each of the official South African languages. Both the activities of AFRILEX and the articles published in Lexikos have a huge influence on the activities of the national lexicography units.Keywords: association, communication, dictionary, feasibility study, journal, language for special purposes, legislation, lexicography, national lexicography units, terminography, terminology